The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1136/bjo.2009.159632
|View full text |Cite
|
Sign up to set email alerts
|

TGFBI mutational analysis in a New Zealand population of inherited corneal dystrophy patients

Abstract: Mutational analysis of TGFBI in a small population has identified sequence changes consistent with previously identified genotype-phenotype correlations. A new genotype-phenotype association was also characterised. No mutations were identified in some individuals/pedigrees suggesting greater genetic heterogeneity than is currently known in this group of disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A previous study on 42 Chinese patients with particular CD subtypes did not detect TGFBI mutations in three patients with clinically diagnosed GCD2; interestingly, whole gene sequencing revealed that GCD2 was caused by non- TGFBI mutations in these patients [ 15 ]. Since TGFBI CD appears to represent a disease spectrum, rather than discrete phenotypes, with increasingly atypical or variant phenotypes, genetic diagnosis sometimes challenges the apparent clinical diagnosis when few TGFBI mutations are found in the atypical group [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on 42 Chinese patients with particular CD subtypes did not detect TGFBI mutations in three patients with clinically diagnosed GCD2; interestingly, whole gene sequencing revealed that GCD2 was caused by non- TGFBI mutations in these patients [ 15 ]. Since TGFBI CD appears to represent a disease spectrum, rather than discrete phenotypes, with increasingly atypical or variant phenotypes, genetic diagnosis sometimes challenges the apparent clinical diagnosis when few TGFBI mutations are found in the atypical group [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 GSN analysis was performed at the National Amyloidosis Centre (University College London, London, UK) Further systemic evaluation included hematologic tests, urine analysis, cardiologic evaluation with echocardiogram and cardiac markers, abdominal ultrasound, and bone marrow and renal biopsies.…”
Section: Methodsmentioning
confidence: 99%
“…Although studies of BIGH3-related HCD are of great interest (3,4), the role of BIGH3 mutations in HCD remains to be fully understood due to the lack of animal models (5). Since there are many limiting factors in the study of HCD, relevant animal models would greatly contribute to the study of this pathogenesis.…”
Section: Introductionmentioning
confidence: 99%